The effect of higher ATP cost of contraction on the metabolic response to graded exercise in patients with chronic obstructive pulmonary disease - Layec, G.; Haseler, Luke; Richardson, R. (The American Physiological Society, 2012)
To better understand the metabolic implications of a higher ATP cost of contraction in chronic obstructive pulmonary disease (COPD), we used 31 P-magnetic resonance spectroscopy ( 31 P-MRS) to examine muscle energetics and pH in response to graded exercise. Specifically, in six patients and six well-matched healthy controls, we determined the intracellular threshold for pH (T pH ) and inorganic phosphate-to-phosphocreatine ratio (T Pi/PCr ) during progressive dynamic plantar flexion exercise with work rate expressed as both absolute and relative intensity. Patients with COPD displayed a lower peak power output (WRmax) compared with controls (controls 25 ± 4 W, COPD 15 ± 5 W, P = 0.01) while end-exercise pH (controls 6.79 ± 0.15, COPD 6.76 ± 0.21, P = 0.87) and PCr consumption (controls 82 ± 10%, COPD 70 ± 18%, P = 0.26) were similar between groups. Both T pH and T Pi/PCr occurred at a significantly lower absolute work rate in patients with COPD compared with controls (controls: 14.7 ± 2.4 W for T pH and 15.3 ± 2.4W for T Pi/PCr ; COPD: 9.7 ± 4.5W for T pH and 10.0 ± 4.6Wfor T Pi/PCr , P > 0.05), but these thresholds occurred at the same percentage of WRmax (controls: 63 ± 11% WRmax for T pH and 67 ± 18% WRmax for T Pi/PCr ; COPD: 59 ± 9% WRmax for TpH and 61 ± 12% WRmax for T Pi/PCr , P > 0.05). Indexes of mitochondrial function, the PCr recovery time constant (controls 42 ± 7 s, COPD 45 ± 11 s, P = 0.66) and the PCr resynthesis rate (controls 105 ± 21%/min, COPD 91 ± 31%/min, P = 0.43) were similar between groups. In combination, these results reveal that when energy demand is normalized to WRmax, as a consequence of higher ATP cost of contraction, patients with COPD display the same metabolic pattern as healthy subjects, suggesting that skeletal muscle energy production is well preserved in these patients.